Impact of grid spacing, convective parameterization and cloud microphysics in ICON simulations of a warm conveyor belt - Choudhary, Anubhav; Voigt, Aiko (Copernicus, 2022)
Warm conveyor belts are important features of extratropical cyclones and are characterized by active diabatic processes. Previous studies reported that simulations of extratropical cyclones can be strongly impacted by the horizontal grid spacing. Here, we study to what extent and in which manner simulations of warm conveyor belts are impacted by the grid spacing. To this end, we investigate the warm conveyor belt (WCB) of the North Atlantic cyclone Vladiana that occurred around 23 September 2016 and was observed as part of the North Atlantic Waveguide and Downstream Impact Experiment. We analyze a total of 18 limited-area simulations with the ICOsahedral Nonhydrostatic (ICON) model run over the North Atlantic that cover grid spacings from 80 to 2.5 km, including those of current coarse-resolution global climate models with parameterized convection, as well as those of future storm-resolving climate models with explicit convection. The simulations also test the sensitivity with respect to the representation of convection and cloud microphysics. As the grid spacing is decreased, the number of WCB trajectories increases systematically, WCB trajectories ascend faster and higher, and a new class of anticyclonic trajectories emerges that is absent at 80 km. We also diagnose the impact of grid spacing on the ascent velocity and vorticity of WCB air parcels and the diabatic heating that these parcels experience. Ascent velocity increases at all pressure levels by a factor of 3 between the 80 and 2.5 km simulations, and vorticity increases by a factor of 2 in the lower and middle troposphere. We find a corresponding increase in diabatic heating as the grid spacing is decreased, arising mainly from cloud-associated phase changes in water. The treatment of convection has a much stronger impact than the treatment of cloud microphysics. When convection is resolved for grid spacings of 10, 5 and 2.5 km, the above changes to the WCB are amplified but become largely independent of the grid spacing. We find no clear connection ...